Assessment of knowledge and practices of menstrual hygiene among urban adolescent girls in North India - Gandotra, Nikita; Pal, Reena; Maheshwari, Sonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Menstruation and menstrual practices are still associated with socio-cultural restriction and taboos which results lack of knowledge and awareness in adolescent girls and remain ignore of scientific facts and hygienic practices during menstruation leads to severe reproductive health problems. The aim of the study is to assess the knowledge and menstrual hygiene practices among urban adolescent girls. Methods: A cross sectional observational study conducted. Total 120 adolescent girls enrolled in this study who were attended in gynaecological OPD. A structured questionnaire was used for data collection. Data was collected regarding menstrual cycle, knowledge about menstruation, practices during menstruation and menstrual hygiene. Data entry and analysis was carried out in Microsoft excel and analysis done by using frequency. Results: All participants were doing schooling, most of them they have done their high school study (47.5%) and 52.5% of adolescent girls were attended menarche between 10-13 yrs of age. Majority of participants were knowing about the menstruation before menarche (62.5%). Friends followed by mothers were the major sources of knowledge i.e.35% and 27.5% respectively. 22.5% of adolescent girls still using cloth as menstrual absorbent. Conclusions: All adolescent girls should be educated about the menstruation, physiological implications, its significance and proper hygienic practices during menstruation. Incorrect restrictions, myths and beliefs associated with menstruation can be removed by the help of parents, teachers, trained school nurses/ health personnel.